The Canola Oil Industry and EU Trade Integration: A Gravity Model Approach - Dirk Röttgers; Anja Faße; Ulrike Grote (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Recently biodiesel has become more prominent in countries of the European Union (EU). The rapidly increasing domestic production and consumption of biodiesel is accompanied by increasing trade flows. It is questionable if these trade flows are caused mainly by EU regulations concerning trade or concerning the bioenergy sector. A sector-specific analysis taking industry patterns into consideration is necessary to evaluate the impact of these two policy areas on trade flows. A common way to analyze trade flows is the so-called gravity model, which is employed here. Because of zero-inflated trade data, the model is expanded using the Heckman approach and augmented by spatial weights and Anderson & Van Wincoop's controls for multilateral resistance. The obtained results suggest that while the mandatory biofuel blending quota has a positive impact, investment subsidies cannot be shown to have any effect and trade integration might even have a trade inhibiting effect among EU members. The surprising latter result can be explained by an exhausted domestic European market for raw and intermediate materials for biodiesel and proves stable even when controlling for sector specific variables.
Keywords: Q17; 330; canola; biofuel; gravity model; trade integration